2010
DOI: 10.1089/end.2010.0128
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Lymph Node Yield After Pelvic Lymph Node Dissection in Men with Prostate Cancer: A Comparison Between Robot-Assisted Radical Prostatectomy and Open Radical Prostatectomy in the Modern Era

Abstract: No significant differences were seen in LNY during RARP and ORP for intermediate and high-risk men. For experienced surgeons, RARP can achieve equivalent LNY as ORP. A future study with a larger sample size is necessary to make a definitive statement of equivalence.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
27
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(29 citation statements)
references
References 23 publications
2
27
0
Order By: Relevance
“…The selected studies are consistent with prior publications with mean estimated blood loss (EBL) ranging from 50 to 200 mL and 450 to 1,200 mL for RALP and RRP, respectively [6][7][8][9]. RALP is consistently associated with a decreased need for blood transfusion, with transfusion rates ranging from 0% to 5.1% versus 3% to 65% for RRP [6, 7, 10-13, 14••, 15-17].…”
Section: Blood Losssupporting
confidence: 81%
See 3 more Smart Citations
“…The selected studies are consistent with prior publications with mean estimated blood loss (EBL) ranging from 50 to 200 mL and 450 to 1,200 mL for RALP and RRP, respectively [6][7][8][9]. RALP is consistently associated with a decreased need for blood transfusion, with transfusion rates ranging from 0% to 5.1% versus 3% to 65% for RRP [6, 7, 10-13, 14••, 15-17].…”
Section: Blood Losssupporting
confidence: 81%
“…Four studies compared LND in RALP and RRP, three of which observed statistically significant higher lymph node yields (LNY) in the RRP groups [13,35,36]. Mean LNY was 6 to 14.4 in RRP patients and 7.1 to 9.3 in RALP patients [9,35,36]. Although not statistically significant, one study trended toward a higher mean LNY in RRP, but was ultimately underpowered due to small sample size [9].…”
Section: Nodesmentioning
confidence: 97%
See 2 more Smart Citations
“…[11][12][13] Moreover, recent reports have demonstrated that PLND during RALP provided a high lymph node yield and appeared to have minimal morbidity compared with the open technique. [13][14][15] Therefore, we assessed whether the extent of PLND at RALP had any benefit on lymph node yield, staging accuracy, and biochemical recurrence (BCR) in patients with high-risk prostate cancer.…”
Section: Introductionmentioning
confidence: 99%